4-Amino-5-(2-hydroxyphenyl)-2H-1,2,4-triazole-3(4H)-thione - Dinçer, M; Özdemir, N; Çetin, A; Cansiz, A; Sekerci, M (Int Union Crystallography, 2005)
In the title compound, C8H8N4OS, the planar triazole ring is effectively coplanar with the benzene ring, which facilitates the formation of three intramolecular interactions N-H center dot center dot center dot S ( leading to a thione tautomer in the solid state), O-H center dot center dot center dot N and C-H center dot center dot center dot N. Intermolecular N-H center dot center dot center dot S interactions lead to the formation of dimers, which are, in turn, linked to each other by N-H center dot center dot center dot O hydrogen bonds.
Keywords: Spin-Transition